Influence of resin cement thickness and temperature variation on mechanical behavior of dental ceramic fragment restoration - Martini, Ana Paula [UNESP]; de Souza, Fernando Isquierdo [UNESP]; Anchieta, Rodolfo Bruniera [UNESP]; de Almeida, Erika Oliveira; Freitas Junior, Amilcar Chagas; Rocha, Eduardo Passos [UNESP] (Taylor & Francis, 2019)
To evaluate the stress behavior of ceramic fragment restoration, varying the thickness of the cement layer and intraoral temperature variation. A solid model of a upper lateral incisor was obtained and a defect at enamel distal/incisal edge was restored with a ceramic fragment. Based on this initial model, 4 different models (M) were built: M1–absence of cement layer (CL) (0 μm of thickness); M2–CL with an uniform thickness of 50 μm; M3–CL with 50 μm at the margin of ceramics and 100 μm in the inner area far from margins; M4–CL with 50 μm at the margin of ceramics and 200 μm in the inner area far from margins. The environment temperature changed from 5 °C to 50 °C in 4 increments. The finite element analysis was performed. Increase the cement layer thickness generated higher stress levels on ceramic surface in all temperatures, as well as on cement interface. In general hot temperature was the worst scenario for ceramic fragments integrity, since tensile and compressive stress were more intense. The maximum principal stress on ceramic fragment was found 90 MPa for M4 at 50 °C, followed for M3 (87 Mpa). For CL, the peak of stress was found for M3 at 5 °C (47 MPa). Is it possible to conclude that thick resin cement layer contribute to higher stress concentration on ceramic fragment, and extremely hot temperatures increase the risk of structural failure, since both ceramic and \cl are exposed to higher compressive and tensile stresses.
Keywords: ceramic fragment;; Dental ceramic; finite element analysis; minimally invasive dentistry; resin cement;